Animal Welfare Assessment Protocol for Does, Bucks, and Kit Rabbits Reared for Production - Dalmau, Antoni; Moles, Xenia; Pallisera, Joaquim (Frontiers in Veterinary Science, 2020)
Rabbits are the third species in terms of number of animals reared for meat production in the world. However, in comparison to other species, very few studies have focused on their welfare. The aim of the present study is to implement an animal welfare-assessment protocol developed through a multidimensional approach and containing a number of animal-based measures for bucks, does and kit rabbits. Thirty Spanish farms with conventional cages in the first year of integration in an animal welfare certification scheme were visited during2019 and audited by the same auditor. The protocol is divided into four principles and 11 criteria. The Good Feeding principle includes eight parameters (one animal-based); Good Housing includes 15 parameters (six animal-based), Good Health includes 26 parameters (16 animal-based) and Appropriate Behaviour contains nine parameters (four animal-based). In general, the main problems found were the absence of platforms, low space allowance and low height of the cage, inappropriate systems for performing emergency killing, insufficient protection of does from other adjacent does when housed individually and absence of enrichment material. To a minor degree, but also found in an important number of farms, was a lack of temperature data records, high replacement rates of does and lack of mortality-rate data records. However, in general, most of the farms obtained a good overall score, the maximum found being 73 out of 100 points. Nevertheless, none of the farms reached an excellent score, and four farms were scored below the 55 points required in the animal welfare certification scheme. The Good Feeding principle obtained the highest score, reaching excellent in all farms, and Appropriate Behaviour the lowest one, with values ranging from 21 to 41 points out of 100. The results probably show how, for years, rabbit producers have been very focused on feeding needs and very little attention has been paid to behavioural needs.